Dynamic Logic. New Trends and Applications : Second International Workshop, DaLí 2019, Porto, Portugal, October 7–11, 2019, Proceedings /: Second International Workshop, DaLí 2019, Porto, Portugal, October 7–11, 2019, Proceedings. (2020) - Unknown
No abstract available